Comparative Study Of Fastness Properties And Color Absorbance Criteria Of Conventional And Avitera Reactive Dyeing On Cotton Knit Fabric - Sufian, Md. Abu; Hannan, Md.Abdul; Rana, Md. Masud; Huq, Muhmmad Zanibul (European Scientific Journal, ESJ, 2016)
160 GSM Single Jersey cotton knitted fabric was dyed with conventional Remazol reactive dye and latest Avitera reactive dye (Huntsman). Detailed comparison of the process parameters and fastness properties of these dyed fabrics were studied. Investigation exposed that Avitera delivered better dyeing performance including fastness to washing, perspiration, rubbing than conventionally dyed fabrics. Concerning process parameters Avitera dye required less soda, salt and no addition of other auxiliaries. Also this new Avitera reactive dye is more eco-friendly, cost effective and energy saving than conventional Remazol reactive dye. CMC DE and Da* color deviation were significantly higher between the dyed samples. Again K/S value of Avitera dyed sample was superior to that of Remazol dyed samples as because of enhanced dye uptake. Sequentially reflectance and relative indicators of the latest reactive dyed samples were also experimented.